A review: microstructure and properties of tin-silver-copper lead-free solder series for the applications of electronics. Issue 2 (14th October 2019) - Aamir, Muhammad; Muhammad, Riaz; Tolouei-Rad, Majid; Giasin, Khaled; Silberschmidt, Vadim V.
Abstract : Purpose: The research on lead-free solder alloys has increased in past decades due to awareness of the environmental impact of lead contents in soldering alloys. This has led to the introduction and development of different grades of lead-free solder alloys in the global market. Tin-silver-copper is a lead-free alloy which has been acknowledged by different consortia as a good alternative to conventional tin-lead alloy. The purpose of this paper is to provide comprehensive knowledge about the tin-silver-copper series. Design/methodology/approach: The approach of this study reviews the microstructure and some other properties of tin-silver-copper series after the addition of indium, titanium, iron, zinc, zirconium, bismuth, nickel, antimony, gallium, aluminium, cerium, lanthanum, yttrium, erbium, praseodymium, neodymium, ytterbium, nanoparticles of nickel, cobalt, silicon carbide, aluminium oxide, zinc oxide, titanium dioxide, cerium oxide, zirconium oxide and titanium diboride, as well as carbon nanotubes, nickel-coated carbon nanotubes, single-walled carbon nanotubes and graphene-nano-sheets. Findings: The current paper presents a comprehensive review of the tin-silver-copper solder series with possible solutions for improving their microstructure, melting point, mechanical properties and wettability through the addition of different elements/nanoparticles and other materials. Originality/value: This paper summarises the useful findings of the tin-silver-copper series comprehensively. This information will assist in future work for the design and development of novel lead-free solder alloys.